Medial Prefrontal Cortical Dopamine Responses During Operant Self-Administration of Sweetened Ethanol - Doherty, James M. (Alcohol Clin Exp Res, 2016)
BACKGROUND: Medial prefrontal cortex (mPFC) dysfunction is present in heavy alcohol consumers. Dopamine signaling in mPFC is associated with executive functioning and affects drinking behavior; however, direct measurement of extracellular mPFC dopamine during appetitive and consummatory ethanol (EtOH) self-administration behavior has not been reported. METHODS: We used in vivo microdialysis in freely behaving, adult, male, Long Evans rats to determine extracellular dopamine concentration in the mPFC during operant self-administration of an EtOH-plus-sucrose or sucrose solution. The model separated appetitive/seeking from consummatory phases of the operant session. Dopamine was also monitored in an untrained handling control group, and dialysate EtOH was measured in the EtOH-drinking group. RESULTS: Home cage baseline dopamine was lower in rats that experienced a week of drinking sweetened EtOH compared with sucrose-drinking and handling controls. Transfer into the operant chamber and the initiation of consumption stimulated a relatively higher change in dopamine over baseline in the sweetened EtOH group compared with sucrose and handling controls. However, all groups show a dopamine response during transfer into the operant chamber, and the sucrose group had a relatively higher change in dopamine over baseline during initiation of consumption compared with handling controls. The time courses of dopamine and EtOH in the mPFC differ in the EtOH-consuming rats. CONCLUSIONS: Differences in extracellular mPFC dopamine between EtOH drinkers compared with control groups suggest that mPFC dopamine is involved in the mechanism of operant self-administration of sweetened EtOH and sucrose. Furthermore, the increase in dopamine during consumption is consistent with a role of mPFC dopamine in reward prediction.